A new soft coral species from the Gulf of Mexico (Octocorallia: Scleralcyonacea: Parasphaerascleridae) - Quattrini, Andrea M.; Morrissey, Declan; Mccartin, Luke J. (Zootaxa, 2025)
A new species of soft coral, Parasphaerasclera mcfaddenae (Octocorallia: Scleralcyonacea: Parasphaerascleridae), is described from mesophotic hardbottom habitats of the Gulf of Mexico, western North Atlantic Ocean. Previously, this family was only known from the tropical Indo-Pacific and South Africa; therefore, we extend the distribution of the family Parasphaerascleridae into the North Atlantic Ocean. This diminutive species differs from other parasphaerasclerids by a capitate growth form, non-retractile polyps, and presence of tuberculated spindles. Notably, this species was also detected in environmental (e)DNA samples from locations where it was not physically collected, highlighting the importance of both eDNA for biodiversity surveys as well as specimen collections for building comprehensive reference databases for eDNA analyses.